PENDIDIKAN KARAKTER BERORIENTASI HIGHER ORDER THINKING SKILLS PADA MATA KULIAH BIOTEKNOLOGI DI STKIP RIAMA MEDAN - Jimmy Francius Simbolon (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
Higher order thinking skills (HOTS) in learning is the application of thinking processes to complex situations and has many variables. Students can think, but most of the students need encouragement and guidance for high-level thinking processes. High-level thinking skills are very necessary in the current era of globalization. Complex thinking skills will make students accustomed to facing something difficult. Through the implementation of HOTS-oriented character education, students have good character values, namely discipline, hard work, creative and independent. In addition to having good character, students are also able to evaluate, create and have creations so that learning outcomes are expected to be better when compared to conventional methods.